12909 Wörter (Hamburg : Hochschule für bildende Künste Hamburg, 2003)
Altmann, Moritz ; Appel, Helene ; Bartholin, Mette ; Christoffel, Claudia ; Grahlmann, Insa ; Jurin, Katarina-Zrinka ; Grau, Anna Lena ; Hauberg, Stefan ; Köster, Daniela ; Klumpp, Nora May ; Krüger, Lutz ; Limantara, Cindya ; Matthes, Mark ; Oh, Setbyol ; Rindfleisch & Rapedius ; Vordermaier, Sonja ; Zarius, Sebastian
Publicatie bij het seminarie van Prof. Dr. Noemi Smolik van 2003-04-11 tot 2003-07-18
Duits
boek